Análise de fragilidade ambiental com métodos multicritério - críticas e proposta metodológica - Cereda Junior, Abimael (2011)
The attempt to understand the environment through techniques for posterior modifications and interventions is a fact that, for some researchers, made man, human. The understanding on which surrounds a group of individuals can lead, however, to a deterministic reading or even to a superposition, lacking criteria, of the elements in consideration, which leads to distortions in understanding the complex system called environment. Therefore, it s not enough that the gathering of data, and its simple overlap exists, and for spatial data, the accumulation of maps. There is the need of, technical, social and economical criteria to improve understanding, as well as a conceptual-methodological discussion regarding the representation of the Geographical Space. Throughout methodological theories and orientations, such grasp can be achieved by the understanding of, not only one component, but the integration of all components, like in Synthesis Cartography. So, the methods are necessary for the reorganization, transforming data in information (and information onto knowledge), allowing that managers and population can think, analyze and act onto the Space they are inserted in. Thereunto, the multi-criteria methods allows breaking with the statistical representations of the environment, overcoming the inventory paradigm, been that one of the purposes of the present theses, from assumptions of the Environmental Fragility and the utilization of multi-criteria methods of Weighted Linear Combination and Ordered Weighted Averaging, which generates the Map of Environmental Fragility for part of the watershed of Monjolinho River in São Carlos - SP, anchored on the Eco-dynamical approach. Likewise, besides the cartographical product which can subsidize actions from the public power, it was possible the verification of hypotheses that the introduction of one of these methods, from its correct understanding and articulation, allows it to step up to the main purpose of Synthesis Cartography and Planning, be it urban or environmental: the re-integration of variables that concretize territorially in a unison an non-isolated manner, which throughout the Ordered Weighted Averaging method can lead to the transfer of collective technical intelligence, to a Geographic Information System.